Impact of Financial Development on Exchange Rate Volatility and Long-Run Growth Relationship of Bangladesh - Bristy, Humyra Jabeen (International Journal of Economics and Financial Issues, 2014)
Empirical results show that exchange rate volatility has a negative impact on the economic growth of Bangladesh. In contrast, this paper endeavors to analyze whether level of financial development of Bangladesh has any impact on the exchange rate volatility and growth relationship. To test this, Ordinary Least Square technique has been used considering the interaction between financial development and exchange rate volatility. The findings of the study confirm that growth of this country is adversely affected by exchange rate variability because of the poorly developed financial market of Bangladesh. As the level of financial development is thin, anticipation of exchange rate fluctuations discourages innovation which in turn lowers the growth of Bangladesh. Hence, despite of exchange rate controls have been in place for a long time, those trades oriented policies failed to raise the long run growth of Bangladesh. Keywords: Exchange rate volatility; growth; financial development JEL Classifications: F4; 01